PENGARUH PROFITABILITAS, LEVERAGE, FIRM SIZE DAN DIVIDEN PAYOUT RATIO TERHADAP NILAI PERUSAAN MANUFAKTUR YANG LISTED DI BURSA EFEK INDONESIA TAHUN 2017-2018 - Sarina Hi Djafar; Nur Hidayati; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the effect of profitability, leverage, firm size and dividend payout ratio on the value of manufacturing companies listed on the Stock Exchange in 2017-2018. This type of research is a type of quantitative research. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange, the sampling technique uses a purposive sampling method. Based on predetermined criteria, a sample of 50 companies was obtained with an observation period of 2 years. The analytical method used in this study is multiple linear analysis. The data used in this study is a secondary data type. The results of the study show that profitability and leverage affect the value of the company while firm size and dividend payout ratio do not affect the value of the company. Simultaneously profitability, leverage, firm size and dividend payout ratio have a significant effect on firm value. Keywords: Profitability, Leverage, Firm Size, Dividend Payout Ratio, Value Company